2003
DOI: 10.1097/01.ccm.0000080487.20304.2e
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide infusion improves ischemic renal failure after suprarenal abdominal aortic cross-clamping in dogs

Abstract: The present study shows that ANP infusion preserved renal function after suprarenal abdominal aortic cross-clamping in dogs. These results justify a trial of ANP infusion in humans during aortic aneurysm repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…12 ANP is a circulating hormone that is synthesized and released by the cardiac atria in response to volume expansion or cardiac hypoxia, after which it provides vasodilating and natriuretic properties. 13 ANP administered before ischemia has demonstrated protective effects against I/R injury in the heart, 13-15 liver 16 -20 and kidney, 21,22 and the protective mechanisms are not yet fully understood. In the only previous study on ANP and I/R injury, no effect was seen on PVR or lung weight gain.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…12 ANP is a circulating hormone that is synthesized and released by the cardiac atria in response to volume expansion or cardiac hypoxia, after which it provides vasodilating and natriuretic properties. 13 ANP administered before ischemia has demonstrated protective effects against I/R injury in the heart, 13-15 liver 16 -20 and kidney, 21,22 and the protective mechanisms are not yet fully understood. In the only previous study on ANP and I/R injury, no effect was seen on PVR or lung weight gain.…”
Section: Discussionmentioning
confidence: 95%
“…4 -12 Several forms of atrial natriuretic peptide (ANP) offer protective effects against I/R injury in various organs other than lung. [13][14][15][16][17][18][19][20][21][22] The favorable effects of ANP have been ascribed to activating guanylate cyclase and increasing tissue cGMP levels. 14,15,20 In the lung, protective effects of ANP have been reported against chemical-, oxidant-and high-altitude-induced lung injuries.…”
mentioning
confidence: 99%
“…Our group recently demonstrated an hANP-induced preservation of renal function after suprarenal abdominal aortic cross-clamping in a dog model approximating ischemic acute renal injury after abdominal aortic aneurysm repair (21). Low-dose hANP infusion reduced postoperative complications after cardiovascular surgery in clinical studies (22,25).…”
Section: Discussionmentioning
confidence: 98%
“…In our own study we demonstrated an hANP-induced improvement of ischemic renal failure after suprarenal abdominal aortic cross-clamping in a dog model (21). Additionally, a clinical study by Swärd et al (22) found that a low-dose infusion of hANP enhanced renal excretory function, decreased the probability of dialysis, and improved dialysis-free survival in ischemic acute renal failure after complicated cardiac surgery.…”
mentioning
confidence: 86%
“…In the past decade, different kinds of medicines, such as prostaglandins, "renal-dose" dopamine and atrial natriuretic factor, have been tried to treat patients with ischemic ARF and these animal models. Although some of these agents have improved renal function, urine output and even renal histological impairment in patients and animal models, few studies have demonstrated that these medicines can reduced the mortality of the disease [15][16][17][18] . In the present study, we found that applying this specific ICE inhibitor in the initial term of the disease remarkably increased the survival rate in this animal model.…”
Section: Discussionmentioning
confidence: 99%